Serving the Moral Agenda - Joan Gordon (Humanimalia, 2011)
Review of: Tom Regan and Andrew Linzey, eds. Other Nations: Animals in Modern Literature. Waco, TX: Baylor UP, 2010. xx + 214 pp. $29.95 pbk.